PROFIL PASIEN KANKER YANG MENJALANI RADIOTERAPI DI RUMAH SAKIT UNIVERSITAS ANDALAS PADANG TAHUN 2019-2020PROFIL PASIEN KANKER YANG MENJALANI RADIOTERAPI DI RUMAH SAKIT UNIVERSITAS ANDALAS PADANGTAHUN 2019-2020 - Muhammad Azzel Hanggara; Fathiya Juwita Hanum; Adrial Adrial (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Background: Cancer is a non-communicable disease, which is one of the causes of death. In the future, it is predicted that this cancer will continue to increase, especially in developing countries, including Indonesia. Methods: This study is a descriptive observational study with a retrospective approach. The sampling method in this study was total sampling with the number of samples in this study being 510 samples. The instrument used in this study is secondary data from medical records. The data obtained will be processed and presented in the form of distribution tables and graphs. Results: According to the findings of this study, the majority of cancer patients who received radiotherapy were between the ages of 45 and 54 (30.78%), and the female population was larger than the male population, at 72.5 percent versus 27.5 percent, respectively. %), the majority of patients came from the province of West Sumatra (80.5%), and the most common occupation was housewife (44.8%). Stage IV is the most common stage (26.1%), and the highest anatomical pathology result is invasive carcinoma of no special type (breast cancer) .Conclusion: Based on the results of this research, it can be concluded that the distribution of patients based on gender was more female than male. The distribution of patients based on domicile, who came from West Sumatra Province is the highest. Distribution in West Sumatra Province which consists of districts and cities, Padang City was the highest with a number of patients. The distribution of patients based on age shows that the most common age ranges for cancer patients are 45-54 years and 55-64 years. The distribution of cancer patients in terms of occupation, the majority are housewives (IRT) as many as 227 people (44.5%), civil servants, TNI Polri as many as 70 people (13.7%), private sector and self-employed as many as 61 people (12.0%).